2018
DOI: 10.1016/j.ejvs.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow up of Patients with Acute Aortic Syndromes: Relevance of both Aortic and Non-aortic Events

Abstract: Among patients with either type A or type B AAS surviving the acute phase, the risk of adverse aorta and non-aorta related events, including death, persists during follow up, so that eventually two thirds of patients will experience at least one event. Notably, all cause mortality after type B AAS exceeds that of type A AAS after three years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Taken altogether, these findings would suggest a pattern of early intensive care for aortic complications and later care needs for cardiovascular events. Furthermore, they are similar to those from a recent series at the University of Bologna (Italy) detailing the long-term followup of 242 consecutive patients with final diagnosis of acute AS between 2010-2016, which reported that two thirds of these individuals will eventually develop at least one aortic or nonaortic event during long-term follow-up 8 . We believe follow-up should be based on careful multidisciplinary assessment, to be made on a case by case basis, and eventually lead to a patient-tailored protocol encompassing at least the frequency and consistency of imaging (with a balance to be achieved between the need to detect even subtle changes of the disease pattern and the necessity to keep radiation and contrast exposure as low as reasonable), early referral for intervention and strict management of cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 83%
“…Taken altogether, these findings would suggest a pattern of early intensive care for aortic complications and later care needs for cardiovascular events. Furthermore, they are similar to those from a recent series at the University of Bologna (Italy) detailing the long-term followup of 242 consecutive patients with final diagnosis of acute AS between 2010-2016, which reported that two thirds of these individuals will eventually develop at least one aortic or nonaortic event during long-term follow-up 8 . We believe follow-up should be based on careful multidisciplinary assessment, to be made on a case by case basis, and eventually lead to a patient-tailored protocol encompassing at least the frequency and consistency of imaging (with a balance to be achieved between the need to detect even subtle changes of the disease pattern and the necessity to keep radiation and contrast exposure as low as reasonable), early referral for intervention and strict management of cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, in the present study, age showed no association with AAE, inconsistent with previous studies. 14 The discordance might be explained by the shorter follow-up period in this cohort.…”
Section: Discussionmentioning
confidence: 83%
“…TEVAR, a valuable option for patients with TBAD, is associated with a high AAE rate during follow-up even after successful operation. Corsini et al 14 reported that the reintervention rate after TEVAR was 35.9% in patients with type B acute aortic syndrome after TEVAR. In the present study, 18.6% of the patients experienced AAE during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors found aortic and cardiovascular causes to be the most common reason for readmission during the early and late follow-up periods, respectively, which is consistent with our findings. In a similar study in Italy, 25 long-term rehospitalization rates for aortic causes and nonaortic cardiovascular causes in patients who underwent surgical repair (OSR, TEVAR, or a hybrid of both) for acute TBAD were 35% and 12.5%, respectively. These studies both showed a high rate of readmission, driven primarily by cardiovascular causes, as seen in our patient cohort.…”
Section: Discussionmentioning
confidence: 87%